Nanocasting synthesis of mesoporous SnO2 with a tunable ferromagnetic response through Ni loading. Issue 106 (2nd November 2016) - Fan, Junpeng; Zhang, Jin; Solsona, Pau; Suriñach, Santiago; Baró, Maria Dolors; Sort, Jordi; Pellicer, Eva
Abstract : Ni-doped SnO2 mesoporous powders exhibit ferromagnetism at low and room temperatures, which can be tuned by adjusting the Ni loading. Abstract : Undoped and Ni-doped ordered mesoporous SnO2 powders ([Ni(ii )]/[Sn(ii )] = 0 : 100, 5 : 95, 15 : 85, 20 : 80) were synthesized by nanocasting from mesoporous KIT-6 silica. The resulting Ni content in the Ni-loaded powders ranged between 1 at% and 9 at%. Successful replication of the silica template was verified by scanning electron microscopies for all samples. Residual silicon content did not surpass 4 at%. X-ray diffraction analyses showed that the powders were nanocrystalline, being the rutile-like phase of SnO2 the dominant structure. Changes in the lattice constants depending on the Ni content were observed, suggesting that Ni enters the rutile structure of SnO2 to some extent. No extra phases attributed to Ni were detected in the powders except for the sample synthesized from 20 : 80 [Ni(ii )]/[Sn(ii )], for which NiO as secondary phase was observed. The oxidation state and spatial distribution of Ni in the powders was investigated by X-ray photoelectron spectroscopy (XPS) and electron energy loss spectroscopy (EELS) measurements, respectively. For 6 at% and 9 at% Ni content, the presence of Ni 2+ was established. The corresponding EELS mapping showed that a fraction of Ni (the one not forming part of the rutile phase) tended to accumulate at the pore edges, forming a nanometer-thick NiO layer. Compared to undoped SnO2, Ni-containing powders exhibit a ferromagnetic response at low and room temperatures. Uncompensated spins at the surface of NiO are likely to contribute, in part, to the observed ferromagnetic properties.